Scavenger Receptor B and CD36 Targeting Improves Sepsis Survival and Acute Outcomes in Mice - Leelahavanichkul, Asada (2012)
Class B scavenger receptors, such as SR-BI/II or CD36, bind lipoproteins, but also mediate bacterial recognition and phagocytosis. In evaluating whether blocking receptors can prevent intracellular bacterial proliferation, phagocyte cytotoxicity and proinflammatory signaling in bacterial infection/sepsis, we found that SR-BI/II- or CD36-deficient phagocytes are characterized by a reduced intracellular bacterial survival, a lower cytokine response, and were protected from bacterial cytotoxicity in the presence of antibiotics. Mice deficient in either SR-BI/II or CD36 are protected from antibiotic-treated cecal ligation and puncture (CLP)-induced sepsis, with greatly increased peritoneal granulocytic phagocyte survival (8-fold), a drastic diminution in peritoneal bacteria counts and 50 to 70% reduction in systemic inflammation (serum levels of IL-6, TNF-α and IL-10) and organ damage relative to CLP in wild-type mice. CD36-deficient mice survival after CLP was 58% compared to 17% in control mice. When compensated for mineralocorticoid and glucocorticoid deficiency, SR-BI/II-deficient mice had almost a 50% survival rate vs. 5% in mineralo-/glucocorticoid-treated controls. Targeting SR-B receptors with L-37pA, a peptide that functions as an antagonist of SR-BI/II and CD36 receptors, also increased peritoneal granulocyte counts, reduced peritoneal bacteria and bacterium-induced cytokine secretion. In the CLP mouse sepsis model L-37pA improved survival from 6% to 27%, reduced multiple organ damage, and improved kidney function. These results demonstrate that the reduction of both SR-BI/II- and CD36-dependent bacterial invasion and inflammatory response in the presence of antibiotic treatment results in granulocyte survival, local bacterial containment, and also reduces systemic inflammation, organ damage and improve animal survival during severe infections.